Concrete and sustainability - Jahren, Per, 1939-; Sui, Tongbo (CRC Press, Taylor and Francis Group ; Chemical Industry Press, 2014)
"Concrete is the second most common commodity in the world, after water, and by far the most common building material. The industry has a great deal of responsibility for sustainable development. This book demonstrates the importance of sustainable thinking, examines the range of challenges facing the concrete engineer, and outlines how they can be addressed. It balances account resource availability, technical viability, economical feasibility, environmental sustainability and social responsibility. It presents a holistic view of the environmental challenges and conveys the complexity of the topic, while giving examples of good practice in various aspects from around the world"--